Palmar Basal Cell Carcinoma in Darker Skin Tone Patient: A Case Study - Nada Alghamdi; Bader Algamdi; Ahmed A. Alsaati; Areej M. Al Nemer (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)